Soil biota, antimicrobial resistance and planetary health - Zhu, Yong-Guan; Zhao, Yi; Zhu, Dong; Gillings, Michael; Penuelas, Josep; Ok, Yong Sik; Capon, Anthony; Banwart, Steve (Environment international, 2019)
The concept of planetary health acknowledges the links between ecosystems, biodiversity and human health and well-being. Soil, the critical component of the interconnected ecosystem, is the most biodiverse habitat on Earth, and soil microbiomes play a major role in human health and well-being through ecosystem services such as nutrient cycling, pollutant remediation and synthesis of bioactive compounds such as antimicrobials. Soil is also a natural source of antimicrobial resistance, which is often termed intrinsic resistance. However, increasing use and misuse of antimicrobials in humans and animals in recent decades has increased both the diversity and prevalence of antimicrobial resistance in soils, particularly in areas affected by human and animal wastes, such as organic manures and reclaimed wastewater, and also by air transmission. Antimicrobials and antimicrobial resistance are two sides of the sword, while antimicrobials are essential in health care; globally, antimicrobial resistance is jeopardizing the effectiveness of antimicrobial drugs, thus threatening human health. Soil is a crucial pathway through which humans are exposed to antimicrobial resistance determinants, including those harbored by human pathogens. In this review, we use the nexus of antimicrobials and antimicrobial resistance as a focus to discuss the role of soil in planetary health and illustrate the impacts of soil microbiomes on human health and well-being. This review examines the sources and dynamics of antimicrobial resistance in soils and uses the perspective of planetary health to track the movement of antimicrobial-resistance genes between environmental compartments, including soil, water, food and air. •The review uses “One Health” perspective to track the movement of ARGs.•Soil and soil fauna microbiomes are the source of bioactive compounds.•Soil biota has the diverse and abundant intrinsic resistome.•Human activities are increasing antibiotic resistome at the global scale.•Management of soil biota is vitally important for safeguarding planetary health.